2021
DOI: 10.1029/2020je006515
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Shear Flow Over Large Martian Ripples

Abstract: Aeolian ripples are abundant in arid regions on Earth and on the surface of Mars. On Earth, wind of sufficient strength can begin mobilizing sand grains into "saltation" (bouncing) trajectories that disturb other grains on the bed with every rebound, quickly leading to a cascading mobilization of many other grains. In fully developed saltation, shear stress at the bed is reduced by momentum exchange between the boundary layer and numerous grains in flight, so that continued grain mobilization from the bed is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…On Earth, the relatively potent fluid force from the wind limits ripple size. Here, our findings are consistent with the mechanisms suggested by Sullivan and Kok (2017), Sullivan et al (2020), Siminovich et al (2019) and Yizhaq et al (2021) where the lower fluid force of the thin Martian atmosphere does not provide the same height-capping mechanism as on Earth and allows a broader range of ripple scales. There is clear separation in the threshold of motion for grains from adjacent large and small ripples (Figure 5).…”
Section: Resultssupporting
confidence: 91%
“…On Earth, the relatively potent fluid force from the wind limits ripple size. Here, our findings are consistent with the mechanisms suggested by Sullivan and Kok (2017), Sullivan et al (2020), Siminovich et al (2019) and Yizhaq et al (2021) where the lower fluid force of the thin Martian atmosphere does not provide the same height-capping mechanism as on Earth and allows a broader range of ripple scales. There is clear separation in the threshold of motion for grains from adjacent large and small ripples (Figure 5).…”
Section: Resultssupporting
confidence: 91%
“…(2016). Further supporting the latter speculation, recent Computational Fluid Dynamics (CFD) simulations also demonstrated that higher wind kinematic viscosities decrease turbulence within the boundary layer along a range of ripple sizes, such that lower atmospheric densities translate into lower shear stresses at ripple crests, possibly allowing them to grow larger and longer (Siminovich et al., 2019; Yizhaq et al., 2021).…”
Section: Figurementioning
confidence: 82%
“…Together with the longitudinal ripples, the impact mechanism in a low wind dynamic pressure environment can also explain the presence of megaripples and transverse aeolian ridges (TARs-bedforms having width/wavelength of ∼10 m which can be either small dunes or megaripples (Bourke et al, 2010;Zimbelman et al, 2013)), which are not explained by the fluid-drag hypothesis (Lapotre et al, 2016a(Lapotre et al, , 2016bSullivan et al, 2020). The Martian low density boundary layer also imposes lower (compared to Earth) shear velocities over the ripple slopes (Siminovich et al, 2019;Yizhaq, Siminovich, et al, 2021). CFD simulations have been used to investigate if and where shear velocities reach the fluid threshold for sand motion over a synthetic and a more realistic ripple profile (Siminovich et al, 2019;Yizhaq, Siminovich, et al, 2021).…”
Section: The Large Martian Ripplesmentioning
confidence: 99%